Utilizing Artificial Intelligence-based Paraphrasing Tool in EFL Writing Class: A Focus on Indonesian University Students’ Perceptions - Mufida Syahnaz; Rahmah Fithriani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
This study aims to investigate students’ perception of QuillBot utilization in an EFL academic writingcourse. This phenomenological case study involved 20 sixth-semester students majoring in English Education as the participants. Data were collected through an online questionnaire distributed to all of the participants and face-to-face interviews with five participants who were purposefully selected based on their responses to the questions in the online questionnaire. The results of the data analysis reveal that the students exhibited positive responses toward the utilization of QuillBot in academic writing. Furthermore, they also find QuillBot beneficial for three reasons; first, it helps improve the content or argument; second, it minimizes grammatical errors, and third, it enhances the language used in their manuscripts. It could be concluded that integrating artificial intelligence such as online paraphrasing tools helps EFL students overcome some difficulties encountered in writing academic papers, and consequently improve their writing products.This study implies that the use of AI-based technology in language classrooms would be advantageous in a variety of ways; however, further research is required to determine the relative importance of each element regarding students' use of the AI-based paraphrasing tool, particularly QuillBot.